A Note on Relative Backwardness and Industrial Structure - Gregory, Paul R. (Quarterly Journal of Economics, 1974)
Introduction, 520. — Structural bias and relative backwardness: a proposed measurement, 522. — Conclusions, 525. — Appendix, 526.